STRUCTURAL AND MAGNETIC PROPERTIES OF SmCoCu PERMANENT MAGNETS - Awan, M. S.; Manzoor, U.; Bhatti, A. S. (The Nucleus, 2020)
The effect of composition and heat treatment on the intermetallic alloy SmCo5 has been carried out to improve the magnetic properties. The base composition (SmCo5) was modified by substitution of cobalt (Co) with copper (Cu) and annealing the samples under argon atmosphere. Annealed and cast samples revealed mixed-phase microstructure responsible for improved magnetic properties. X-ray diffraction (XRD) confirmed the hexagonal crystal structure of the base alloys. Optical and scanning electron microscopy (SEM) was used to study the formation and effect of annealing on the different phases and was related to the magnetic properties. Energy dispersive X-ray (EDX) was carried out to determine the composition of different phases. Precipitation of copper-rich phase acts as the pinning centers for the domain wall motion. This restriction on domain wall motion improves the magnetic hardening of the base alloy. It was found that Cu diffusion plays a major role in determining the magnetic properties of these magnetic alloys.